REVITALISASI KONSTITUSI DALAM IDEOLOGI TERBUKA PANCASILA - Kertopati, Ton (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2007)
We have been asked to  think  about a convention that will write a new constitution for the Indonesian Republic. What  our reaction?We were surprised  of idea  of a new  constitution? Why?                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                             Do  we assume   the present   constitution/   the first and  oldest  one  w!II remain  in force  forever?Our present   constitution  provides  several  methods   of amendment.   Why didnt the  founding   fathers  include  on amendment  clause?How  did  we react  to  the  suggestion    that  we  were  to participate   in the  new convention?Of course, existence of a certain particular constitutional features are desirable for the nation actual constitutions can provide inspiration but cannot   tell us what is desirable.To  reach conclusions about desirability, we must employ principles of evaluation.These  are serious  doubts   that a new  constitution  should   be helcl obviously  no convention   should  be  called, it can  be  expected   to write a bitter constitution than  we already  have.   Our  constitution   is thus not just  a set of legal  rules, It is also  a paradigm.A paradigm is  an   overall   view   of   things   in   terms   of   which  particular experiences   con be  understoodMost   of  the  young   Indonesian modern generation now days encourages decision   makers  to egotism.Pragmation appears    lo  give  possible   scope    for  the   exercise   of   common sense   new  elements    in  Indonesian    life.    To  be  pragmatic    thus  implies   the opposite  of being  dogmatic    theoretical   or ideological.There is a widespread   belief-Constitution   means  limited government.To be pragmatic as a dogma or  ideological Pancasila appears to  give maximum  scope  the  exercise  of common  sense.As  an  open   ideology   Pancasila  is better  at least  lo stumble   around,   than  to go  in  the  wrong  direction.   Not  such   as  the  Nazis  exterminated  the  Jews,  six. million  of them/  in pursuit  the dogma   or ideology  of  "ryan  Purity".Or the old German marxis  had a slogan: "Und willst  du   nicht   mein brudersein,    so  sch lag   ich  dir  den   scheidel   ein" (If you dont  want   to  be brother,   Ill smack  your  skully).